The notion of energy security in the European Union - Rosicki, Remigiusz (My University, 2012)
In the case of the European Union there is a special notion of energy security, which comprises a number of elements. Energy security is frequently represented as part of energy policy, but we often deal with an overlap of the ideas of energy security and energy policy. The starting point for understanding the notion of the energy policy of the European Union is the supply chain security (i.e. the traditional notion of energy security). First and foremost, the problem of energy supply security was associated with the possibility of satisfying the state-generated demand for energy. However, this mindset soon turned out to be too limited. Energy supply security came to be associated with the social and economic level security, which is expressed in the definition of energy supply security included in the Green Paper of 2001 entitled Towards a European Strategy for the Security of Energy Supply. It reads that energy supply security means ensuring, for the well-being of its citizens and for the proper functioning of the economy, the uninterrupted physical availability of energy products on the market at an affordable price for all consumers (private and industrial ones), whilst respecting environmental concerns and looking towards sustainable development. The main elements that make up the definition are: (1) society, (2) economy, (3) uninterrupted availability of products, (4) prices affordable for consumers, (5) environment, and (6) sustainable development. In a nutshell one might say that energy supply security must allow for three contexts – (1) the social one, (2) the economic one, and (3) the environmental one.
Pojęcie bezpieczeństwa energetycznego w Unii Europejskiej
Keywords: energy security; bezpieczeństwo energetyczne; supply chain security; bezpieczeństwo dostaw; energy policy; polityka energetyczna; energy efficiency; efektywność energetyczna; energy solidarity; solidarność energetyczna; diversification of energy carriers; dywersyfikacja nośników energii; energy market; rynek energii; liberalising the EU energy sector; liberalizacja sektora energetycznego UE; TPA principle; zasada TPA; unbundling; separacja; sustainable development; rozwój zrównoważony; environment; środowisko; demand management; zarządzanie zapotrzebowaniem; the European Union; Unia Europejska